Pre-stroke apathy symptoms are associated with an increased risk of delirium in stroke patients - Klimiec, Elzbieta (Sci Rep, 2017)
Neuropsychiatric symptoms can be interrelated to delirium. We aimed to investigate an association between pre-stroke neuropsychiatric symptoms and the risk of delirium in stroke patients. We included 606 patients (median age: 73, 53% female) with stroke or transient ischemic attack admitted within 48 hours from symptoms onset. We assessed delirium on a daily basis during the first 7 days of hospitalization. To make diagnosis of delirium we used DSM-5 criteria. We used Neuropsychiatric Inventory to assess neuropsychiatric symptoms occurring within 4 weeks prior to stroke. We diagnosed delirium in 28.2% of patients. On univariate analysis, higher score of pre-stroke depression (OR: 1.58, 95% CI: 1.04–2.40, P = 0.03), apathy (OR: 2.23, 95% CI: 1.44–3.45, P < 0.01), delusions (OR: 2.00, 95% CI: 1.09–3.68, P = 0.03), hallucinations (OR: 2.39, 95% CI: 1.19–4.81, P = 0.01) and disinhibition (OR: 2.10, 95% CI: 1.04–4.25, P = 0.04) was associated with the increased risk of delirium. On multivariate analysis adjusted for age, atrial fibrillation, diabetes mellitus, stroke severity, right hemisphere lesion, pre-stroke cognitive decline, pre-stroke disability and infections, higher apathy score (OR: 2.03, 95% CI: 1.17–3.50, P = 0.01), but no other neuropsychiatric symptoms, remained independent predictor of delirium. We conclude that pre-stroke apathy symptoms are associated with increased risk of delirium in stroke patients.